Business continuity strategies : protecting against unplanned disasters - Myers, Kenneth N., 1932- (Wiley, 2006)
With the increased dependency of modern corporations on computer technology and special-purpose facilities, contingency planning is a rising priority on the agenda of senior management. This book provides cost-conscious executives with a structured process to address contingency planning needs.